Faktor-Faktor Manuver Politik Qatar dalam Penguatan Aliansi dengan Iran Pasca Kasus Krisis Diplomatik Qatar tahun 2017 - Cahyani, Sukma Bintang; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Qatar as a small and wealthy country in the Persian Gulf was being hit by serious diplomatic crisis in the past 2017. The Crisis began when Saudi Arabia, Uni Arab Emirat, Bahrain, and Egypt (named as anti Qatar-quartet) accused Qatar for supporting terrorist group and Its alliance with Iran by doing blockade and terminated their diplomatic relations to Qatar. Some resolution efforts have been made to solve the conflict which happened inside the GCC. It was failed, included mediation from Kuwait. This conflict resolution efforts were leaving 13 demands from anti-Qatar Quartet that hurting the independence and sovereignty of Qatar, especially the demand of shutting down Al-Jazeera, to cut relations with Ikhwanul Muslimin and Iran. The real problem started when Qatar rejected those 13 demands and contrary has strengthening its alliance with Iran. The purpose of this research is to explain what are the driving factors of Qatar to take the political risk by strengthening its alliance with Iran rather than recovering its diplomatic relations with anti-Qatar Quartet by comply the 13 demands. The main argument of this research believes that Qatar as a small country is being weakened by the strong power of quartet. It causes the imbalance of power between them so Qatar choose to strengthens its alliance with Iran to increase its power in the crisis to confront the power of anti-Qatar Quartet threats. This research is analyzed using the concept of bandwagoning in the theory framework of neo-realist’s balance of power with qualitative descriptive research methods by using interview and literature review. The Qatar’s alliance strengthening with Iran will be explained by four factors based on theory analysis, such as: security factor, the inefficiency of GCC’s factor, The Trump’s factor and the LNG’S factor. The result is proved that the bandwagon effort of Qatar to Iran in the diplomatic crisis 2017 became the strategic solution for Qatar. In the end Qatar were able to survive and obtain its own security.Together with Iran, Qatar managed to increase its power to face the threats of Anti-Qatar Quartet and keep surviving in the regional structure.